Analisis Behavioral Intention Mobile Banking dengan Model UTAUT2 - Deasy Safitri; Sofyan, Joel Faruk; Negoro, Dimas Angga; Kusmayadi, Andri (Innovative: Journal Of Social Science Research, 2024)
The development of information technology has been very developed at this time, people have started to study and use technology, one of which is mobile banking. Mobile banking allows customers to complete financial transactions electronically without having to interact directly with bank employees. How to use mobile banking can be influenced by several supporting factors. The purpose of this research is to examine and analyze the influence of consumer usage behavior intentions on usage behavior using the UTAUT2 model. Using a purposive sampling method, this study used 145 mobile banking users and distributed online questionnaires from June to July 2023. By applying PLS-SEM as an intervention tool, this study found that performance expectancy, effort expectancy, social influence, facilitating conditions and price values ​​have no effect on behavioral intention, while hedonic motivation and habit have a positive effect. Then behavioral intention has no influence on use behavior.